Kinematic analysis of high jump using the scissors technique - Ljubičić, Sanja (Studia sportiva, 2024)
The purpose of the research is to determine the kinematic parameters that are key to achieving the best high jump results with the scissors technique in children, as well as the mutual correlations in the approach and take-off phases. As many as 123 subjects between the ages of 7 and 12 (AS±SD = 9.20±1.33) participated in the research. The respondents were members of the Kvarner athletics club. The high jump using the scissors technique was recorded with a Sony RX10 II video camera. The kinematic analysis was carried out using the software Kinovea 0.9.5. Multiple linear regression was used to examine the association of nine predictor variables with the bar height criterion, while to determine significant correlations between kinematic parameters, an analysis of Pearson's correlation coefficients was performed. The most significant findings of the research show that the predictors explain a significant part of the variance (60.4 %) of height of the bar (F (9. 112) = 18.98; p < 0.001). Significant predictors of height of the bar are: the duration of the penultimate stride in the run-up (b = - 0.43; p < 0.01), length of the last stride in the run-up (b = 0.30; p < 0.01), length of the penultimate stride in the run-up (b = 0.41; p < 0.01) and ankle angle (b = 0.21; p < 0.01). Certain kinematic parameters are relevant for success in the high jump.